Collaborative Housing: a bibliometric analysis of global patterns and trends in scientific research - Heras Robles, Inmaculada; Ruiz Seisdedos, Susana; Álvarez Nieto, Carmen (REVESCO. Revista de Estudios Cooperativos, 2025)
The article examines the evolution and impact of scientific production on collaborative housing through a bibliometric approach. The use of quantitative statistical methods of data visualization aims to strategically reveal the historical development of fields of subject, patterns of authors, the most relevant journals and their impact indexes, as well as the main themes and their temporal evolution. First, a systematic review of the Scopus database was carried out following the PRISMA statement. Secondly, with the selected articles, data processing was carried out using the Bibliometrix package of the R software and its Biblioshiny graphical interface. The results of the 223 selected articles show a slow but steady growth of publications and a multidisciplinary interest. Bradford’s distribution shows that a dozen scientific publications account for most of the production. The key role of female authorships stands out, both in terms of productivity and impact. The strategic diagram shows the current and future lines of research. The driving themes show three widely developed and key lines for collaborative housing: sustainability, housing policy and collaborative housing for older adults or senior cohousing. Shared housing and covid-19 are currently basic issues, but due to their development they are very close to consolidating themselves as a driving force.